(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
Climate change has been recognized as one of the most critical global challenges of the 21st century, not only for its environmental and ecological consequences but also for its serious impact on human health, particularly mental health. One example of how slow, gradual climate change affects individual mental health is the occurrence of ecological anxiety (eco-anxiety) —a psychological response characterized by feelings of helplessness and fear about the future of the planet. This paper explores the concept of ecological anxiety in Jenny Offill’s novel Weather (2020), while situating this phenomenon within the theoretical framework of necropolitics, as articulated by Cameroonian philosopher Achille Mbembe. The novel functions as a microcosm for exploring the social, political, and existential dynamics of our time, where climate change intensifies structural inequalities and disproportionally exposes marginalized populations to greater ecological risks. The novel Weather narrates the experience of Lizzie Benson, a woman and a mother living in New York who struggles with anxiety of impending environmental disaster. Through an experimental yet highly relatable narrative structure, Offill weaves a subtle critique of the necropolitical systems that determine who is spared from and who is destined to suffer the consequences of climate change. Mbembe’s theory of necropolitics, which extends Foucault’s ideas of biopolitics and biopower, emphasizes the control over life and death. This concept helps us understand how marginalized populations are disproportionally exposed to ecological degradation. This paper analyzes how Offill positions ecological anxiety as a device to explain deeper necropolitical structures. Lizzie Benson’s fear is not personal but symbolic of a larger societal angst, rooted in the unequal distribution of ecological harm: her daily interactions with diverse social groups—from the affluent planning smart escape strategies to marginalized communities who remain vulnerable to climate disasters. The novel subtly states that survival in the face of ecological collapse depends on privilege and access to resources. By situating Weather within the broader context of climate fiction and necropolitical theory, this paper argues that Offill’s work serves both as a literary exploration of ecological anxiety and a critique of the political systems that perpetuate environmental harm. Moreover, Weather challenges readers to reflect on their own complicity in sustaining these systems. Offill’s unique fusion of wit, reflection, and narrative fragmentation captures the complex emotional landscape of living in an age where the future of our planet feels increasingly uncertain.